The Climate Response to Emissions Reductions Due to COVID‐19: Initial Results From CovidMIP. Issue 8 (28th April 2021) - Jones, Chris D.; Hickman, Jonathan E.; Rumbold, Steven T.; Walton, Jeremy; Lamboll, Robin D.; Skeie, Ragnhild B.; Fiedler, Stephanie; Forster, Piers M.; Rogelj, Joeri; Abe, Manabu; Botzet, Michael; Calvin, Katherine; et al.
Abstract: Many nations responded to the corona virus disease‐2019 (COVID‐19) pandemic by restricting travel and other activities during 2020, resulting in temporarily reduced emissions of CO2, other greenhouse gases and ozone and aerosol precursors. We present the initial results from a coordinated Intercomparison, CovidMIP, of Earth system model simulations which assess the impact on climate of these emissions reductions. 12 models performed multiple initial‐condition ensembles to produce over 300 simulations spanning both initial condition and model structural uncertainty. We find model consensus on reduced aerosol amounts (particularly over southern and eastern Asia) and associated increases in surface shortwave radiation levels. However, any impact on near‐surface temperature or rainfall during 2020–2024 is extremely small and is not detectable in this initial analysis. Regional analyses on a finer scale, and closer attention to extremes (especially linked to changes in atmospheric composition and air quality) are required to test the impact of COVID‐19‐related emission reductions on near‐term climate. Plain Language Summary: Many nations responded to the COVID‐19 pandemic by restricting travel and other activities during 2020. This caused a temporary reduction in emissions of CO2 and other pollutants. We compare results from twelve Earth system models to see if the emissions reductions affected climate. These twelve models performed over 300 experiments using multiple initial‐conditions. We find a consensus that aerosol amounts were reduced, especially over southern and eastern Asia, during 2020‐2024. This led to increases in solar radiation reaching the surface in this region. However, we could not detect any associated impact on temperature or rainfall. We recommend more analyses on regional scales. We also suggest that analysis of extreme weather and air quality would be useful to test the impact on climate of emission reductions due to COVID‐19. Key Points: Lockdown restrictions during COVID‐19 have reduced emissions of aerosols and greenhouse gases 12 CMIP6 Earth system models have performed coordinated experiments to assess the impact of this on climate Aerosol amounts are reduced over southern and eastern Asia but there is no detectable change in annually averaged temperature or precipitation